Photosensors based on Ni-doped ZnO/p-Si junction prepared by sol-gel method - Cavas, M.; Farag, A. A. M.; Alahmed, Z. A.; Yakuphanoğlu, Fahrettin (Springer, 2013)
A high quality and adherent transparent layer of ZnO thin films were grown on p-type Si substrates to fabricate undoped and Ni-doped ZnO/p-Si heterojunction. The C-Adj-V and G(Adj)-V plots of the diodes are significantly affected with the frequency and Ni-dopant contents. The interface state density (D-it) is changed with the frequency and Ni contents. The high value of ideality factor (n) is due to the interface states at the interface of the diode and the effect of barrier inhomogeneities or to the high value of R-s. The transient photocurrent measurements were used to analyze the photoresponse of the diodes. The obtained results indicate that the diodes could be used as an optical sensor especially for the Ni-doped at 0.5 % ZnO/p-Si diode.
Keywords: ZnO; Photodiode; Photoresponse; Sol gel method